2014
DOI: 10.1128/jvi.02037-14
|View full text |Cite
|
Sign up to set email alerts
|

Lysine 63-Linked TANK-Binding Kinase 1 Ubiquitination by Mindbomb E3 Ubiquitin Protein Ligase 2 Is Mediated by the Mitochondrial Antiviral Signaling Protein

Abstract: Beta interferon (IFN-␤) is involved in a wide range of cellular functions, and its secretion must be tightly controlled to inhibit viral spreading while minimizing cellular damage. Intracellular viral replication triggers cellular signaling cascades leading to the activation of the transcription factors NF-B and interferon regulatory factor 3 (IRF3) and IRF7 (IRF3/7), which synergistically bind to the IFN-␤ gene promoter to induce its expression. The mitochondrial antiviral signaling protein (MAVS) is a govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Ubiquitination of many other proteins of the RLR signaling pathway has been reported (Gack et al, 2007; Liu et al, 2013; Maelfait and Beyaert, 2012; Tu et al, 2013; Ye et al, 2014); the nature of the ubiquitination linkages on most of these proteins is either K48-linked branches, leading to proteolytic degradation of the target protein, or K63-linked branches leading to its activation in signal transduction (Nakhaei et al, 2009; Zeng et al, 2009). Although degradative ubiquitination of IRF-3 has been described before (Chen et al, 2007; Yu and Hayward, 2010; Zhang et al, 2008), our analysis of RIPA provided an example of activating ubiquitination of IRF-3.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination of many other proteins of the RLR signaling pathway has been reported (Gack et al, 2007; Liu et al, 2013; Maelfait and Beyaert, 2012; Tu et al, 2013; Ye et al, 2014); the nature of the ubiquitination linkages on most of these proteins is either K48-linked branches, leading to proteolytic degradation of the target protein, or K63-linked branches leading to its activation in signal transduction (Nakhaei et al, 2009; Zeng et al, 2009). Although degradative ubiquitination of IRF-3 has been described before (Chen et al, 2007; Yu and Hayward, 2010; Zhang et al, 2008), our analysis of RIPA provided an example of activating ubiquitination of IRF-3.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis demonstrated that TBK1 ubiquitination by MIBs was critical for the recruitment of NEMO and the antiviral response triggered by cytosolic viral RNA [153, 154]. Mechanistically, MIB2 was shown to bind to the adaptor MAVS involving a highly conserved DLAIS motif at amino acid positions 438 to 442 of MAVS; this motif was critical for MIB2-mediated TBK1 ubiquitination and subsequent IRF3/7 phosphorylation by TBK1 [155]. Furthermore, TRAF3 and Nrdp1 have also been shown to mediate TBK1 K63-linked ubiquitination [100, 156].…”
Section: Ubiquitin-dependent Regulation Of Common Downstream Signalinmentioning
confidence: 99%
“…K48 and K63, the lysines at positions 48 and 63 of ubiquitin linked with polyubiquitin chains, are two canonical polyubiquitin chain linkages. A series of cases have reported that the target proteins were degraded by K48-linked polyubiquitin chains in a proteasome-dependent manner, whereas their functions were stabilized and enhanced by K63-linked polyubiquitin chains (35)(36)(37). To dissect the pattern of ubiquitination of MAVS through K48-or K63-linked ubiquitination, cells were cotransfected with MAVS-Flag, Myc-N, HA-Ub-K48O, or HA-Ub-K63O.…”
Section: N Protein Promotes Ubiquitination Of Mavsmentioning
confidence: 99%